Unveiling the Genetic Diversity of Tunisian Monumental Olive Trees to Enhance the Olive Sector - Sameh Rahmani Mnasri; Cinzia Montemurro; Monica Marilena Miazzi; Olfa Saddoud Debbabi (Horticulturae)
The centennial olive trees of Tunisia serve as enduring symbols of resilience, having withstood the test of time while witnessing the effects of climate change, rising temperatures, water scarcity, and the emergence of new diseases. Presently, there is a notable lack of research on the genomic analysis of ancient trees. This study investigates the genetic diversity of twenty-eight ancient olive specimens collected from archeological sites in nine governorates from the north to the south of Tunisia. Using nine highly polymorphic microsatellite markers, these ancient olive trees were compared with twenty-five local Tunisian cultivars and sixty olive varieties from other Mediterranean countries (Greece, Italy, and Spain). The ancient olive trees were revealed to have a high genetic diversity, with 67 alleles and a Shannon index of 1.68. The key findings identify the ancient trees M25, M1, M28, and M24 as synonyms for local olive cultivars, while “M10” is noted as a first-generation migrant from Tunisian olives. Cluster analysis methods, including structure, neighbor-joining (NJ), and principal coordinates (PCoA), show that these ancient trees share a common genetic background and ancestry with varieties from Tunisia, Italy, Spain, and Greece. The conservation and evaluation of these genotypes will increase the genetic diversity available for breeding programs and strengthen the resilience of agriculture, which is currently facing unprecedented pressure worldwide.